Ortaçağ İslam Dünyasında Deri, Tahta ve Kağıt Sanayi - Bakır, Abdulhalik (Türk Tarih Kurumu [EN], 2001)
Deri, insanların çok eski devirlerden beri giyim-kuşam, yeme-içme ve barınma işlerinde kullanmış oldukları eşyaların yapımında önemli bir ham madde olarak tanınmaktadır. Eski Mısırlılar evde yetiştirdikleri veya avlamak suretiyle elde ettikleri hayvanların derilerini ince yumuşak bir hale getirerek onlardan yastık, döşek vb. ev eşyaları ve çeşitli giysiler imal ediyorlardı. Aynı zamanda Mezopotamyalılar deri tabaklama işini büyük bir ustalıkla yapıyorlardı ve onlar derilerin temizlenmesi, parlatılması, daha sonra da boyanması ve onlardan türlü eşyaların yapılmasında özel yöntemler kullanıyorlardı. Ayrıca bu devirde her türlü çömlek, taş, dokuma ve derileri boyamak için çeşitli boyalar icat edilmişti.

From earliest times, leather has constituted an important raw material employed in the making of wearing apparel, vessels for foodstuffs and beverages and shelters. Leatherworking in Yemen and at Taif in the Hejaz region attained a high level of development in the medieval Islamic world. Leather produced here was exported to Iraq, Khorasan, Kirman, Maveraünnehr, Khwarezm and Hejer and, subsequently, dispatched by leather merchants in these places to other parts of the world. Regions noted for their excellence in leatherworking were North and Central Africa, Syria, Iran and Maveraünnehr-the last mentioned place the locus of a dense settlement of Turks. In the thirteenth to fourteenth centuries, Saray Berke the capital of the Golden Horde achieved importance in the production of leather. Under the Seljuks, Diyarbakır and Kastamonu were leading centers of leather manufacturing. Leather manufacturing in Anatolia, which declined during the occupation by the Mongols of Asia Minor, revived in the Ottoman period and laid a foundation for the development of European leather manufacturing. One of the chief uses to which leather was put was bookbinding and because Muslims regarded books as sacred it reached the pinnacle of development in all Islamic states. Turning now to the manufacture of wood products, it should be noted that the wood which was utilized for numerous purposes-from furniture to war machines-was supplied through importation from lands rich in forestry resources. For forested regions being were scant in the Islamic world while those of Egypt, North Africa and Algeria had been destroyed by earlier civilizations. In the medieval era, the use of wood for household furnishings and in shipbuilding exhibited advances particularly in settlements along the shores of the Mediterranean. Finally, concerning the manufacture of paper, Muslims were introduced to paper subsequent to the Battle of Talas in 751 A.D., and its production spread throughout the Islamic World in the ninth and tenth centuries. Invented by the Chinese, the manual production of paper was refined and developed by the Arabs and Turks for some one thousand years before it was introduced to Europe in the thirteenth century, where its manufacture was at once converted to mechanized production.
The Manufacturing of Leather, Wood and Paper in the Medieval Islamic World
Keywords: Archaeology; Arkeoloji